The Long-lasting Shadow of the Allied Occupation of Austria on its Spatial Equilibrium - Christoph Eder; Martin Halla (Institute for the Study of Labor (IZA), 2016)
As a consequence of World War II, Austria was divided into four different occupation zones for 10 years. Before tight travel restrictions came into place, about 11 percent of the population residing in the Soviet zone moved across the demarcation line. We exploit this large internal migration shock to further our understanding of why economic activity is distributed unevenly across space. Our analysis shows that the distorted population distribution across locations has fully persisted until today (60 years after the demarcation line become obsolete). An analysis of more direct measures of economic activity shows an even higher concentration in the former non-Soviet zone. This gap in economic activity is growing over time, mainly due to commuting streams out of the former Soviet zone. This shows that a transitory shock is capable of shifting an economy to a new spatial equilibrium, which provides strong evidence for the importance of increasing returns to scale in explaining the spatial distribution of economic activity.
Keywords: R11; R12; R23; J61; N44; N94; 330; spatial equilibrium; agglomeration effects; population shock; World War II; Austria